Recent advances in macrophage-derived exosomes as delivery vehicles - Shumin Wang; Yajie Yang; Shenhua Li; Haibo Chen; Yongsheng Zhao; Jing Mu (Nano TransMed)
ABSTRACT: Macrophages are important members of the innate immune system that can be reversibly polarized by different microenvironment signals. Exosomes secreted from cells are lipid bilayer membrane vesicles carrying versatile biomolecules, which displays unique properties and biological functions. Recent studies have shown that macrophage derived exosomes as an extracellular vehicle can deliver diverse cargoes including small molecules, nanoparticles, and biological macromolecules to recipient cells, and thus affect the progression of cancers and other diseases. Moreover, exosomes secreted by different phenotypes of macrophages provide different therapeutic options. Thus, in this review, we summarized recent progress in the macrophage derived exosomes as carriers for delivering different types of cargos. Then the engineering principles and their applications are elaborated. In the end, challenges and prospects of macrophage derived exosomes for drug delivery and disease treatment are also discussed.